2015
DOI: 10.1096/fj.14-257931
|View full text |Cite
|
Sign up to set email alerts
|

HDAC1 and HDAC2 collectively regulate intestinal stem cell homeostasis

Abstract: Histone deacetylases (HDACs) are posttranslational modifiers that deacetylate proteins. Despite their crucial role in numerous biological processes, the use of broad-range HDAC inhibitors (HDACi), has shown clinical efficacy. However, undesired side effects highlight the necessity to better understand the biology of different HDACs and target the relevant HDACs. Using a novel mouse model, in which HDAC1 and HDAC2 can be simultaneously deleted in the intestine of adult mice, we show that the simultaneous deleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 36 publications
4
33
0
Order By: Relevance
“…b-Naphtoflavone-dependent induction of Hdac1 and Hdac2 deletion in Ah-Cre mice led to intestinal defects, notably eroded epithelium and erased crypts, reduced proliferation, and decreased numbers of both Paneth and goblet cells. Recently, Zimberlin et al (2015) have demonstrated a similar phenotype by deleting both Hdac1 and Hdac2 in the intestinal epithelium in the same Ah-Cre model. This growth inhibitory phenotype was associated with increased g-H2AX foci formation, indicating increased DNA damage responses and the presence of double-strand breaks (Ivashkevich et al, 2012;Redon et al, 2012).…”
Section: Discussionmentioning
confidence: 83%
“…b-Naphtoflavone-dependent induction of Hdac1 and Hdac2 deletion in Ah-Cre mice led to intestinal defects, notably eroded epithelium and erased crypts, reduced proliferation, and decreased numbers of both Paneth and goblet cells. Recently, Zimberlin et al (2015) have demonstrated a similar phenotype by deleting both Hdac1 and Hdac2 in the intestinal epithelium in the same Ah-Cre model. This growth inhibitory phenotype was associated with increased g-H2AX foci formation, indicating increased DNA damage responses and the presence of double-strand breaks (Ivashkevich et al, 2012;Redon et al, 2012).…”
Section: Discussionmentioning
confidence: 83%
“…Class I HDACs play a role in differentiation and appear to have a high level of functional redundancy. In intestinal stem cells, simultaneous ablation of Hdac1 and Hdac2 leads to loss of differentiated cells, altered polarization, and increased cell death (Turgeon et al, 2013, Zimberlin et al, 2015). Similar phenotypes occur in the hematopoietic system where the loss of Class I HDACs leads to decreased bone marrow cellularity (Wilting et al, 2010) and in certain instances, loss of stem and progenitor cells (Heideman et al, 2014).…”
Section: Regulation Of Stem Cell Function By Histone Modificationsmentioning
confidence: 99%
“…Reports investigating the role of single components of the diet [51], microbiome [26, 77–81], metabolome [66], immune system [81], and stroma [63, 82] on ICP using ex vivo culture are starting to emerge. These have demonstrated an increased understanding of how the environment elicits cellular and epigenetic alterations [83, 84] that are relevant to human health and intestinal diseases. Beyaz et al, using an ex vivo model, recapitulated ex vivo the environment associated with a high fat diet and established a PPARÎŽ -dependent link to an increase in stemness within the intestinal niche that predisposes to CRC.…”
Section: Bringing Ex Vivo Closer To In Vivo: the Next Challengementioning
confidence: 99%